PARAMETRLI TRIGONOMETRIYALÍQ TEŃLEMELERDI SHESHIW USÍLLARÍ - Djumabaev, N.; Mamutova, G. (SCIENCE and SOCIETY, 2021)
In this article presents various methods for solving parametric trigonometric equations. It is very useful to teach students of pedagogical institutes parametric equations after teaching trigonometric equations in the discipline “Methods for solving problems in mathematics”. Methods for solving trigonometric equations have also been used to solve parametric trigonometric equations, but the equation needs to be studied depending on the parameter.